THE USE OF MODERN COMPUTER PROGRAMS IN SPEECH THERAPY CLASSES - Maxmudova Madinaxon Sobirxonovna; Obidjonova Sitoraxon Sulaymon qizi (Bright Mind Publishing, 2025)
This article highlights the importance, possibilities and effectiveness of using modern computer programs in speech therapy classes. Digital technologies help to organize correctional classes with children with speech disorders in a more interesting, interactive and demonstrative way.
Keywords: Speech therapy classes, speech development, speech disorders, computer programs, information and communication technologies (ICT), interactive educational programs, multimedia, articulatory apparatus, sound automation, phonemic hearing, vocabulary.